High-performance hard alloy holding-up hammer and preparation method thereof
By optimizing the process ratio and sintering process of cemented carbide top hammers, the existing cemented carbide top hammers have solved the problem of insufficient performance under high temperature and high pressure conditions, and a cemented carbide top hammer with high fracture toughness, ultra-high hardness and high bending strength is prepared, which is suitable for the production of superhard materials.
Patent Information
- Application Number
- CN202411691301.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
AI Technical Summary
The existing cemented carbide top hammers have poor toughness, low hardness and poor bending performance under high temperature and high pressure conditions, which makes them difficult to apply in the synthesis of superhard materials and have high production costs.
By optimizing the process ratio, 0.8-3μm particle size tungsten carbide fine powder, 0.2-0.8μm particle size tungsten carbide fine powder, metal cobalt powder, chromium carbide powder and carbon powder are used as raw materials, and cemented carbide top hammers are fired under high temperature and high pressure conditions using discharge plasma sintering equipment.
The prepared cemented carbide top hammer has high fracture toughness, ultra-high hardness and high flexural strength, which significantly improves its performance under high temperature and high pressure conditions and is suitable for the production of superhard materials.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of superhard material synthesis and ultrahigh pressure, and in particular relates to a high-performance cemented carbide anvil and a preparation method thereof. Background Art
[0002] Cemented carbide is widely used in industrial production due to its unique properties (such as high hardness, high bending strength, high wear resistance, high thermal conductivity, etc.). Cemented carbide top hammer, as another use of cemented carbide, is a core component and key loss part for superhard material synthesis. Under ultra-high temperature and high pressure conditions, the top hammer needs to have high fracture toughness, ultra-high hardness, high bending strength and thermal stability. At present, the main preparation method of cemented carbide top hammer on the market is low-pressure sintering, and the sintering pressure is ≤10MPa. This pressure can compress the micropores inside the tungsten carbide and make the metal cobalt and tungsten carbide tightly bonded together. However, due to problems with raw material grading, mixing process and sintering method, tiny pores are prone to appear inside the top hammer, resulting in problems such as poor toughness, low hardness and poor bending resistance of the top hammer.
[0003] At present, the pressure bearing limit of the first-level top hammer at room temperature is 7-9 GPa, while under high temperature and high pressure conditions, its bearing limit drops sharply to 5-6 GPa. The main reason is that high temperature will coarsen the cemented carbide grains, thereby causing the cemented carbide to become more brittle and the hardness to decrease. At the same time, high temperature will cause thermal stress inside the cemented carbide, resulting in uneven stress in different parts, leading to problems such as cracks and collapse in the top hammer. This problem not only makes it difficult to use the top hammer in the production of high-quality diamond composite sheets, cubic boron nitride, polycrystalline wire drawing dies and other superhard materials, but also increases the production cost of the enterprise, which is an important factor restricting the development of the superhard material industry. Therefore, it is particularly urgent to develop a cemented carbide top hammer with high fracture toughness, ultra-high hardness and high bending strength. Based on this, this application was developed. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-performance cemented carbide top hammer through formula optimization and process adjustment, which solves the problems of poor toughness, low hardness, poor bending resistance and the like of the existing cemented carbide top hammer.
[0005] The present invention also provides a method for preparing the above-mentioned high-performance cemented carbide top hammer, which optimizes the process ratio and uses spark plasma sintering equipment to produce a cemented carbide top hammer with good fracture toughness, high hardness and high bending strength under high temperature and high pressure conditions.
[0006] To achieve the above object, the present invention adopts the following technical solution: A high-performance cemented carbide anvil, which is mainly made of the following raw materials in percentage by weight: 0.8-3μm tungsten carbide powder 70-80%, 0.2-0.8μm tungsten carbide powder 15-25%, metal cobalt powder 3-10%, chromium carbide powder 0.1-0.6%, carbon powder 0-0.5%.
[0007] Specifically, the particle size of the metal cobalt powder includes but is not limited to 0.2-1 μm.
[0008] Specifically, the particle size of the chromium carbide powder includes but is not limited to 0.8-3 μm.
[0009] Specifically, the particle size of the carbon powder includes but is not limited to 0.2-0.8 μm.
[0010] The present invention provides a method for preparing the above-mentioned high-performance cemented carbide top hammer, which comprises the following steps: Step 1: Weigh each raw material in proportion to obtain a mixture, put it into a hard alloy ball mill, then add anhydrous ethanol and paraffin to mix by ball milling, and dry it after the ball milling to obtain a processed powder; Step 2: Put the powder obtained after drying in step 1 into a mold, and perform pre-pressing treatment using a cold isostatic press to obtain a cemented carbide blank; Step 3: placing the cemented carbide blank obtained in step 2 in a vacuum carbon tube furnace for high-temperature dewaxing treatment to obtain a dewaxed blank; Step 4: performing anti-carburization treatment on the dewaxed green body obtained in step 3 to obtain a cemented carbide green body to be sintered; Step 5: placing the cemented carbide blank to be sintered obtained in step 4 in a mold for spark plasma sintering to obtain a cemented carbide top hammer.
[0011] Specifically, in step 1, 15-30% of the weight of the mixture is anhydrous ethanol and 1-3% of the weight of the mixture is paraffin. The ball-to-material ratio used in the ball milling is 2-6:1, the ball milling speed is 200-400 r / min, and the ball milling time is 10-20h. The material of the grinding ball is tungsten-cobalt material YG8, and its diameter includes 10mm, 6mm, and 2mm, and the weight ratio of the three is 4-5:2-3:1.
[0012] Specifically, in step 2, the pre-pressing pressure is 200-400 MPa, and the pressing time is 3-10 min; in step 3, the dewaxing temperature is 600-900° C., and the dewaxing time is 2-10 h. During the cold isostatic pressing process, in order to ensure the size accuracy, density and pressing uniformity of the green body, when the material is loaded into the mold, vibration loading and vacuum packaging are adopted.
[0013] Furthermore, in step 4, the anti-carburizing coating is prepared by the following steps: titanium dioxide, silicon dioxide, and tungsten powder are mixed in a weight ratio of 8-12:1:1, and then 4-6% of the weight of the materials are added with anhydrous ethanol and stirred thoroughly to obtain the anti-carburizing coating; the anti-carburizing coating is evenly applied to the surface of the dewaxed blank with a fine brush, and then placed in a vacuum drying oven for drying, and finally a cemented carbide blank to be sintered is obtained. During the preparation of the anti-carburizing coating, the particle size of the titanium dioxide is 500±50nm, the particle size of the silicon dioxide is 800±50nm, and the particle size of the tungsten powder is 0.5-1μm.
[0014] Furthermore, in step 5, the sintering pressure is 20-60 MPa, the sintering temperature is 1250-1550° C., and the sintering time is 10-60 min.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts metal cobalt powder as the main binder, mainly because metal cobalt can completely infiltrate tungsten carbide, can effectively bond tungsten carbide particles together, and can adjust the brittleness of tungsten carbide itself, and improve the toughness of cemented carbide. Chromium carbide, as a grain inhibitor, can solve the problem of reduced hardness of tungsten carbide caused by grain growth during sintering, and can reduce the probability of sample defects caused by grain growth. The principle is mainly that the eutectic temperature of chromium carbide and metal cobalt is very low, and chromium carbide can be completely dissolved in the bonding phase, thereby preventing the precipitation rate of tungsten carbide in the bonding phase, thereby inhibiting the growth of tungsten carbide particles. Carbon powder, as an antioxidant, can effectively neutralize the oxygen adsorbed on the surface of the raw material, and can significantly affect the liquidus point of tungsten carbide, increase the speed of cemented carbide densification, and improve the hardness and wear resistance of cemented carbide.
[0016] The present invention uses tungsten carbide powder (0.8-3μm, 0.2-0.8μm) of different particle sizes, metal cobalt powder, chromium carbide powder, and carbon powder as raw materials, and uses a spark plasma sintering process to sinter under high temperature and high pressure (pressure 20-60MPa, temperature 1250-1550℃) conditions to produce a cemented carbide anvil with excellent performance. This makes up for the problems of poor toughness, poor hardness, poor bending resistance, etc. of cemented carbide anvils on the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is an electron microscope image of the cemented carbide top hammer obtained in Example 2; Figure 2 This is an electron microscope image of the fracture surface of the quality alloy top hammer prepared in Example 2. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.
[0019] In the following examples, the raw materials used are all commercially available products or can be prepared by conventional methods in the art.
[0020] In the embodiment, the particle size of the metal cobalt powder used is 0.2-1 μm, the particle size of the chromium carbide powder is 0.8-3 μm, and the particle size of the carbon powder is 0.2-0.8 μm.
[0021] Room temperature refers to 25±5°C.
[0022] Example 1 This example provides a method for preparing a high-performance cemented carbide top hammer, and the specific steps are as follows: Step 1: Raw material preparation: According to the weight percentage, tungsten carbide powder with a particle size of 0.8-3μm accounts for 72wt.%, tungsten carbide powder with a particle size of 0.2-0.8μm accounts for 21.2wt.%, metal cobalt powder accounts for 6wt.%, chromium carbide powder accounts for 0.3wt.%, carbon powder accounts for 0.5wt.%, and the sum of the weight percentages of the above components is 100%. After weighing the above components in proportion, put them into a cemented carbide ball mill, and then add 18wt.% anhydrous ethanol and 1wt.% paraffin into the tank according to the total weight of the added powder, and mix and stir. The ball-to-material ratio used in ball milling is 3:1, the ball milling speed is 300r / min, the ball milling time is 12h, and after the ball milling stops. Put the stirred powder into a vacuum drying oven and dry it to finally obtain the dried powder.
[0023] The grinding balls are made of tungsten-cobalt material YG8, with diameters of 10mm, 6mm, and 2mm, and a weight ratio of 4:2:1.
[0024] Step 2: Put the dried powder into a mold and pre-press it with a cold isostatic press to finally obtain a cemented carbide blank, wherein the pressure of the cold isostatic press is 200 MPa and the holding time is 5 minutes.
[0025] Step 3: Place the cemented carbide blank obtained in step 2 in a vacuum carbon tube furnace for high-temperature dewaxing treatment. The dewaxing temperature is 700° C. and the insulation time is 8 hours to obtain a dewaxed blank.
[0026] Step 4: Apply anti-carburizing coating to the surface of the dewaxed blank obtained in step 3 for anti-carburizing treatment, and then place it in a vacuum drying oven for drying to obtain a cemented carbide blank to be sintered. Specifically, the anti-carburizing coating is prepared by the following steps: titanium dioxide, silicon dioxide, and tungsten powder are mixed in a weight ratio of 10:1:1, and then 5% of the weight of the material is added. Anhydrous ethanol is stirred and mixed thoroughly; the anti-carburizing coating is evenly applied to the surface of the dewaxed blank with a fine brush, and then placed in a vacuum drying oven for drying, and finally the cemented carbide blank to be sintered is obtained. During the preparation of the anti-carburizing coating, the particle size of the titanium dioxide is 500nm, the particle size of the silicon dioxide is 800±50nm, and the particle size of the tungsten powder is 0.5-1μm.
[0027] Step 5: Place the hard alloy blank to be sintered obtained in step 4 in a graphite mold and perform spark plasma sintering. The sintering pressure is 50MPa and the temperature is 1200°C. Preferably, when the temperature rises to 900°C, the sintering pressure is reduced to 30MPa, and the temperature is continued to rise to the target temperature and kept for 60 minutes. After the heat preservation is completed, the temperature is reduced to 600°C at a cooling rate of 80°C / min, and then cooled to room temperature after 10 seconds. Finally, a hard alloy top hammer is obtained.
[0028] The cemented carbide top hammer blank prepared by the above method was ground and polished to finally obtain a cemented carbide top hammer sample with a dense and uniform microstructure. The sample was tested for mechanical properties, and its fracture toughness was 12.2MPa·m 0.5 , Rockwell hardness is 94.5 and flexural strength is 3850MPa.
[0029] Example 2 This example provides a method for preparing a high-performance cemented carbide tool, and the specific steps are as follows: Step 1: Raw material preparation: According to the weight percentage, the proportion of tungsten carbide powder with a particle size of 0.8~3μm is 75wt.%, the proportion of tungsten carbide powder with a particle size of 0.2~0.8μm is 16.5wt.%, the proportion of metal cobalt powder is 8wt.%, the proportion of chromium carbide powder is 0.2wt.%, and the sum of the weight percentages of the above components is 100%. After weighing the above components in proportion, put them into a carbide ball mill, and then add 23wt.% anhydrous ethanol and 2wt.% paraffin into the tank according to the total weight of the added powder, and mix and stir. The ball-to-material ratio used in ball milling is 5:1. Anhydrous ethanol is added as a lubricant during the ball milling process. The ball milling speed is 300r / min, and the ball milling time is 18h. After the ball milling stops. Put the stirred powder into a vacuum drying oven for drying, and finally obtain the dried powder.
[0030] Among them, the material of the grinding balls is tungsten-cobalt material YG8, with diameters of 10mm, 6mm, and 2mm, and the weight ratio of the three is 5:3:1.
[0031] Step 2: Put the dried powder into a mold and pre-press it with a cold isostatic press to finally obtain a cemented carbide blank. The pressure of the cold isostatic press is 300 MPa and the holding time is 5 minutes.
[0032] Step 3: Place the cemented carbide blank obtained in step 2 in a vacuum carbon tube furnace for high-temperature dewaxing treatment. The dewaxing temperature is 900° C. and the insulation time is 2 h. Finally, a dewaxed blank is obtained.
[0033] Step 4: Apply anti-carburizing coating to the surface of the dewaxed green body obtained in step 3 for anti-carburizing treatment, and then place the green body in a vacuum drying oven for drying to obtain a cemented carbide green body to be sintered. Specific reference is made to the relevant steps of Example 1.
[0034] Step 5: Place the hard alloy blank to be sintered obtained in step 4 in a graphite mold for spark plasma sintering. The sintering pressure is 45MPa and the temperature is 1350°C. When the temperature rises to 1100°C, the sintering pressure is reduced to 27MPa, and the temperature is continued to rise to the target temperature and kept warm for 30 minutes. After the insulation is completed, the temperature is reduced to 600°C at a cooling rate of 80°C / min, and then cooled to room temperature after 10 seconds to finally obtain a hard alloy top hammer.
[0035] Figure 1 The electron microscope image of the cemented carbide top hammer prepared in Example 2 is given; Figure 2 The electron microscope image of the fracture surface of the alloy top hammer prepared in Example 2 is given. It can be seen from the figure that the metal cobalt is evenly dispersed between the tungsten carbide particles, the tungsten carbide particles and the metal cobalt are tightly bonded, the sintered sample has no defects such as pores, decarburization, carburization, etc., the sintered sample has a uniform and dense structure, and the tungsten carbide particles have no obvious growth phenomenon.
[0036] The cemented carbide tool blank prepared by the above method was ground and polished to finally obtain a cemented carbide top hammer sample with a dense and uniform microstructure. The surface electron microscope image is shown in Figure 1 , fracture surface electron microscope picture see Figure 2 The sample was tested for mechanical properties and its fracture toughness was 13.5 MPa·m 0.5 , Rockwell hardness is 93.5 and flexural strength is 4050MPa.
[0037] The data obtained in the above embodiment are compared and analyzed with the products of a well-known manufacturer at home and abroad, and the results are shown in Table 1.
[0038] As can be seen from Table 1, the performance of the cemented carbide top hammer prepared by the present invention is significantly improved in the same grade (YG6). Compared with the performance of the top hammer of domestic manufacturers. The fracture toughness, hardness and bending strength are increased by 16.37%, 2.15% and 7.71% respectively. Compared with the top hammer of foreign manufacturers, the fracture toughness, hardness and bending strength are increased by 13.44%, 1.71% and 3.71% respectively. The top hammer prepared in this embodiment has better fracture toughness, higher hardness and higher bending strength, mainly based on the following two points.
[0039] 1. The present invention adopts a more reasonable particle grading and additive ratio to ensure that tungsten carbide and metal cobalt can be effectively bonded together. At the same time, the grain inhibitor chromium carbide and antioxidant carbon powder can effectively inhibit the growth of tungsten carbide grains and oxidation of raw materials, ultimately ensuring the excellent performance of the sample.
[0040] 2. The present invention adopts a spark plasma sintering process, and its sintering pressure (20MPa~60MPa) is significantly higher than the pressure of the low-pressure sintering furnace (gas pressure <10MPa) currently used by major cemented carbide top hammer manufacturers. Under high temperature and high pressure conditions, the softened raw materials can be fully squeezed and compacted, and finally a uniform and dense cemented carbide top hammer is obtained.
Claims
1. A high performance cemented carbide top hammer, characterized in that: Mainly made of the following raw materials in weight percentage: 0.8-3μm tungsten carbide powder 70-80%, 0.2-0.8μm tungsten carbide powder 15-25%, metal cobalt powder 3-10%, chromium carbide powder 0.1-0.6%, carbon powder 0-0.5%.
2. The high performance cemented carbide top hammer according to claim 1, characterized in that: The particle size of the metal cobalt powder is 0.2-1 μm.
3. The high performance cemented carbide top hammer according to claim 1, characterized in that: The particle size of the chromium carbide powder is 0.8-3 μm.
4. The high performance cemented carbide top hammer according to claim 1, characterized in that: The particle size of the carbon powder is 0.2-0.8 μm.
5. The method for preparing a high performance cemented carbide top hammer according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: Weigh each raw material in proportion to obtain a mixture, then add anhydrous ethanol and paraffin wax to mix by ball milling, and dry after the ball milling to obtain a processed powder; Step 2: Put the powder obtained after drying in step 1 into a mold, and perform pre-pressing treatment using a cold isostatic press to obtain a cemented carbide blank; Step 3: placing the cemented carbide blank obtained in step 2 in a vacuum carbon tube furnace for dewaxing treatment to obtain a dewaxed blank; Step 4: performing anti-carburization treatment on the dewaxed green body obtained in step 3 to obtain a cemented carbide green body to be sintered; Step 5: placing the hard alloy blank to be sintered obtained in step 4 in a mold for spark plasma sintering.
6. The method for preparing a high performance cemented carbide top hammer according to claim 5, characterized in that: In step 1, 15-30% of anhydrous ethanol and 1-3% of paraffin wax are added based on the weight of the mixture.
7. The method for preparing a high performance cemented carbide top hammer according to claim 5, characterized in that: In step 2, the pre-pressing pressure is 200-400 MPa, and the pressing time is 3-10 min; in step 3, the dewaxing temperature is 600-900° C., and the dewaxing time is 2-10 h.
8. The method for preparing a high performance cemented carbide top hammer according to claim 5, characterized in that: In step 4, the anti-carburizing coating is prepared by the following steps: titanium dioxide, silicon dioxide, and tungsten powder are mixed in a weight ratio of 8-12:1:1, and then 4-6% of the weight of the materials are added with anhydrous ethanol and mixed evenly; the anti-carburizing coating is evenly applied to the surface of the dewaxed blank with a brush, and then placed in a vacuum drying oven for drying, and finally a cemented carbide blank to be sintered is obtained.
9. The method for preparing a high performance cemented carbide top hammer according to claim 8, characterized in that: The particle size of the titanium dioxide is 500±50nm, the particle size of the silicon dioxide is 800±50nm, and the particle size of the tungsten powder is 0.5-1μm.
10. The method for preparing a high performance cemented carbide anvil according to claim 5, characterized in that: In step 5, the sintering pressure is 20-60 MPa, the sintering temperature is 1250-1550° C., and the sintering time is 10-60 min.